State Entrepreneurship in Interwar Poland - Kaliński, Janusz (Studia Historiae Oeconomicae, 2023)
State entrepreneurship, or rather statism, was a strongly developed phenomenon in the economy of interwar Poland. Initially, its source was the legacy of the partition period in the form of the considerable assets of the partitioned states, numerous industrial plants, banks, transport infrastructure, forests and land. In a reborn Poland, in order to strengthen the economy and military potential, the authorities undertook, among other things, a number of industrial investments, developed state-owned banking and transport enterprises and organised profitable treasury monopolies. The share of the state sector in the economy reached 20%, and in some areas even 100%. Researchers of state entrepreneurship, usually, have emphasised its considerable economic efficiency and important social role.